Dung mimicry: the function of volatile emissions and corolla patterning in fly‐pollinated Wurmbea flowers. Issue 5 (9th August 2020) - Johnson, Steven D.; Sivechurran, Jadine; Doarsamy, Sachin; Shuttleworth, Adam
Summary: It has been suggested that flowers of some angiosperms mimic vertebrate faeces (dung) in order to exploit insect pollinators that utilize faeces as a source of food and/or oviposition sites. We investigated a potential case of mimicry in Wurmbea elatior (Colchicaceae), a lily that exhibits a faecal odour and pattern of dark spots on the corolla. We found that W. elatior is pollinated by a broad assemblage of coprophagous flies and is dependent on pollinator visits for seed production. The flowers emit volatiles that are characteristic of vertebrate faeces, and three of these compounds – skatole, indole, and an unidentified compound – elicited electrophysiological antennal responses from flies. Artificial flowers laced with indole and skatole or skatole alone attracted the same assemblage of flies as was recorded on flowers of W. elatior . Spotted artificial flowers attracted twice as many flies as did those lacking spots. Experimental addition of indole and skatole to flowers of Wurmbea kraussii, a congener with unscented flowers pollinated by hoverflies, induced a shift to an insect visitor assemblage dominated by coprophagous flies. This study clarifies the roles of volatile emissions (particularly skatole) and visual signals in floral dung mimicry.